The relationship between workload and the risk of musculoskeletal disorders in dentists practicing in padang city: Cross-sectional study - Apriliyanti, Apriliyanti; Surya, Leny Sang (Padjadjaran Journal of Dental Researchers and Students, 2024)
ABSTRACT Introduction: One of the factors that affect musculoskeletal disorders in dentists is workload. Workload is the number of patients handled by dentists at the practice. The purpose of the study was to determine the relationship between workload and the risk of musculoskeletal disorders in the practice of dentists in Padang City. Methods: This type of research is a quantitative analytical research using a cross-sectional design. The population in the study is all dentists in Padang City who already have a SIP PDGI Padang City branch in 2023 as many as 40 samples using a simple random sampling technique. The data analysis technique in this study used univariate and bivariate analysis which was analyzed using SPSS. Results: This study had 40 respondents who received the most workload frequency distribution of >5 patients/day, namely 28 people (70.0%) and the frequency distribution of the most musculoskeletal disorders risk was moderate, namely 22 people (55.0%) in the practice of dentists in Padang City. Conclusion: There is a relationship between workload and the risk of musculoskeletal disorders in dentists in Padang City as seen from the results of the chi square test.KEY WORDS: workload, dentist, musculoskeletalHubungan beban kerja dengan risiko gangguan muskuloskeletal pada  dokter gigi yang berpraktik: studi cross-sectionalABSTRAKPendahuluan:  Salah satu faktor yang mempengaruhi gangguan muskuloskeletal pada dokter gigi adalah beban kerja. Beban kerja adalah jumlah pasien yang ditangani oleh dokter gigi pada tempat praktik. Tujuan penelitian untuk mengetahui hubungan beban kerja terhadap risiko gangguan muskuloskeletal pada praktek dokter gigi di Kota Padang. Metode: Jenis penelitian ini adalah penelitian kuantitatif analitik dengan menggunakan desain cross-sectional. Populasi pada penelitian adalah seluruh dokter gigi di Kota Padang yang sudah mempunyai SIP PDGI cabang Kota Padang pada tahun 2023 sebanyak 40 sampel dengan menggunakan teknik simple random sampling. Teknik analisis data pada penelitian ini menggunakan analisis univariat dan bivariat yang dianalisis menggunakan SPSS. Hasil: Penelitian ini memiliki 40 responden yang mendapatkan distribusi frekuensi beban kerja terbanyak adalah >5 pasien/hari yaitu 28 orang (70,0%) dan distibusi frekuensi dari risiko gangguan muskuloskeletal terbanyak adalah sedang yaitu 22 orang (55,0%)  pada praktek dokter gigi di Kota Padang. Simpulan: Ada hubungan beban kerja terhadap risiko gangguan musculoskeletal pada dokter gigi di Kota Padang dengan dilihat dari hasil  uji chi square.KATA KUNCI: beban kerja, dokter gigi, muskuloskeletal